Electronic technology as an artistic medium in the Malaysian visual arts practices / Wan Jamarul Imran Wan Abdullah Thani - Wan Abdullah Thani, Wan Jamarul Imran (Institute of Graduate Studies, UiTM, 2012)
Presently, the approach of electronic technology in art practices and the creation of electronic artwork in the Malaysian Art Scene are considered a common scenario. Most artists who practice on electronic artwork have made the electronic technological medium as an expansion of existing media in visual art practices. This research explores the approach of electronic technological medium in the practice of electronic artwork. The purpose of the research is to develop a better understanding on the significance of electronic technology in art practices as well as the progress. This research was employed the qualitative research methodology, which focuses on interviews and documentation analysis as a data collection.